2021
DOI: 10.1097/j.pain.0000000000002537
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of squint as a sensitive assay of sex-dependent calcitonin gene–related peptide and amylin-induced pain in mice

Abstract: An automated facial detection and eye tracking program can measure pain caused by formalin hind paw injection or migraine-inducing compounds in mice. Calcitonin gene–related peptide and amylin induce significant squint behavior responses that are more predominant in female mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The grimace scale was developed to evaluate spontaneous pain expression in mice ( 50 ). Our laboratory found that orbital tightening, or squint, is the principal component of mouse grimace score ( 51 ) and has developed an automated video-based squint assay to measure spontaneous pain ( 48 ). Taking advantage of this sensitive automated squint platform, we asked whether mice squint after CGRP injection in the MN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grimace scale was developed to evaluate spontaneous pain expression in mice ( 50 ). Our laboratory found that orbital tightening, or squint, is the principal component of mouse grimace score ( 51 ) and has developed an automated video-based squint assay to measure spontaneous pain ( 48 ). Taking advantage of this sensitive automated squint platform, we asked whether mice squint after CGRP injection in the MN.…”
Section: Resultsmentioning
confidence: 99%
“…This assay is to evaluate spontaneous pain by measuring the right-eye pixel areas recorded by a camera. Mice were acclimated to a customized collar restraint to reduce stress induced by restraint as well as struggle or head movement as described previously ( 48 ). C57BL/6J mice underwent acclimation for 20 min per session for three sessions.…”
Section: Methodsmentioning
confidence: 99%
“…This assay is to evaluate spontaneous pain by measuring the right-eye pixel areas recorded by a camera. Mice were acclimated to a customized collar restraint to reduce stress induced by restraint as well as struggle or head movement as described previously (81). C57BL/6J mice underwent acclimation for 20 min per session for three sessions.…”
Section: Automated Squint Assaymentioning
confidence: 99%
“…The grimace scale was developed to evaluate spontaneous pain expression in mice (84). Our laboratory found that orbital tightening, or squint, is the principal component of mouse grimace score (85) and has developed an automated video-based squint assay to measure spontaneous pain (81). Taking advantage of this sensitive automated squint platform, we asked whether mice squint after CGRP injection in the MN.…”
Section: Injection Of Cgrp Into the Mn Induced Squinting Behavior Primarily In Female Micementioning
confidence: 99%
See 1 more Smart Citation